2015
DOI: 10.1007/s11064-015-1670-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imipramine, Paroxetine, and Lithium Carbonate on Neurobehavioral Changes of Streptozotocin in Rats: Impact on Glycogen Synthase Kinase-3 and Blood Glucose Level

Abstract: Recent studies have demonstrated a scrutinized association of diabetes mellitus with depressive symptoms and major depression. Glycogen synthase kinase-3 (GSK-3) is a protein kinase enzyme constitutively active in non-stimulated cells and in multiple signalings. Independent lines of research provide a converging evidence for an involvement of GSK-3 in the regulation of behavior and hyperglycemia. The present study revealed that streptozotocin (STZ)-induced diabetic rats were found to show lengthened duration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, it was suggested that beneficial effect on sleep patterns might be synergistic to other mechanisms elicited by quetiapine toward the antidepressant therapeutic, when added to classical antidepressants or as monotherapy [61]. Other studies have found that imipramine, a classic antidepressant, reduced immobility in the forced swimming test in diabetic rats, while also reduced locomotor activity in the open field [7,40]. Still, regarding the effects of locomotor activity, some studies suggest that reduction of motor activity in the open field is correlated with increased immobility, whereas other authors have shown that locomotor activity is not underlying the performance of animals in the forced swim test [11].…”
Section: Effect Of MD and Treatment With Quetiapine On Behavior In Thmentioning
confidence: 99%
“…In addition, it was suggested that beneficial effect on sleep patterns might be synergistic to other mechanisms elicited by quetiapine toward the antidepressant therapeutic, when added to classical antidepressants or as monotherapy [61]. Other studies have found that imipramine, a classic antidepressant, reduced immobility in the forced swimming test in diabetic rats, while also reduced locomotor activity in the open field [7,40]. Still, regarding the effects of locomotor activity, some studies suggest that reduction of motor activity in the open field is correlated with increased immobility, whereas other authors have shown that locomotor activity is not underlying the performance of animals in the forced swim test [11].…”
Section: Effect Of MD and Treatment With Quetiapine On Behavior In Thmentioning
confidence: 99%
“…Each rat received 10 mg/kg/day DH. 35 The first group received DH solution by oral gavage, the second group received the optimized DH-TENV gel, and the third group received the control DH gel. Gel (1 g) was spread over 4 cm 2 of the dorsal surface of the relevant rats after shaving.…”
Section: Pharmacokinetic Analysis Of the Optimized Dh-tenvmentioning
confidence: 99%
“…In rodents, chronic Li treatment modulates the mRNA levels of several genes in the brain [40,41]. Li also decreases GSK3b activity, and enzyme level in the rat hippocampus [42]. Similarly, the observed increases in rat hippocampal vesicle associated membrane protein 2, syntaxin1a, synaptophysin, synaptosome-associated protein 25, synuclein, and cysteine string protein alpha after Li treatment, as well as the increase of synapsin 1 in the rat prefrontal cortex, are consistent with a Li effect on neurotransmitter re- [43,44].…”
Section: Animal Modelsmentioning
confidence: 99%